Strategi Penerapan Self - Management Terhadap Model Belajar Pada Anak Melalui Konseling Individu Di Jalan Gunung Kawi VI, RT .02/ RW.10,Joglo. Kadipiro,Surakarta Tahun 2021 : Strategi Penerapan Self - Management Terhadap Model Belajar Pada Anak Melalui Konseling Individu Di Jalan Gunung Kawi IV, RT. 02/ RW.10, Joglo, Kadipiro, Surakarta tahun 2021 - Fitria Ayu Rohmatullailiyah; Lydia Ersta Kusumaningtyas (MEDIKONS, 2021)
The research objectives are 1) to determine self – management in children through individual counseling, 2) to determine the process of applying self – management in controlling oneself and time to learning models, 3) to find out the supporting factors and obstacles in providing self – management to children through individual counseling services, 4) to determine the impact of self – management through individual counseling services. This research was conducted on jl.Gunung Kawi IV Rt 02/ Rw 10 Joglo, Kadipiro Surakarta.The research method used is descriptive qualitative research. Two sources of data are primary data and secondary data. Primary data sources are the subjects used are clients and counselees, parents of clients, and relatifes or families of clients. While the secondary data sources are through documentation, client identity, data sources,and archives regarding clients, primary and secondary data sources that are obtained directly. Collecting research data using several data collection techniques such as data observation techniques, interview techniques, and documentation techniques. The observation technique was carried out derectly with the subject and then continued with the interview technique with the client or the subject being studied, the client’s parents, and the client’s relatives or family, and was strengthened by research documentation. The data analysis technique used source triangulation and technical triangulation. Intractive data analysis method such as 1) data collection, 2) data reduction, 3) data presentation, 4) conclusion. Based on the data analysis , it can be obtained that on Jl.Gunung Kawi IV Rt 02 / Rw 10 Joglo has 10 children. There are 2 children who cannot manage themselves and time. The two children will be given individual counselling services in their learning model. After implementing self – management through the provision of individual counseling services, there was an increase in the subject. Subjects can manage themselves in learning and can manage time while studying because each subject has a different learning model. The conclusing of this study showed that self – management and time were increased after the subjects were given individual counseling services. Key words: Strategy, Self - management, Learning Model, Individual Counseling Service.